Studi Komparatif Diversifikasi Aset, Pertumbuhan Aset, ROA pada Bank Konvensional dan Syariah - Habsyah Fitri Aryani; Ruli Bestari (Media Ilmiah Akuntansi, 2021)
Since the beginning of its appearance, Islamic banks have experienced significant growth so that they are able to compete with conventional banks. Operationally, Islamic banks and conventional banks have differences. This study is to test whether there are differences in asset growth, asset diversification and Return on Assets (ROA) between Islamic banks and conventional banks. The samples in this study are Islamic and conventional banks which are owned by the State. In testing the variables using the independent sample t-test. The results showed that the asset growth between Islamic banks and conventional banks had no difference. Asset diversification and return on assets between Islamic banks and conventional banks have differences.